2018
DOI: 10.2147/ott.s171714
|View full text |Cite
|
Sign up to set email alerts
|

Huge borderline phyllodes breast tumor with repeated recurrences and progression toward more malignant phenotype: a case report and literature review

Abstract: BackgroundPhyllodes tumor (PT) is a rare breast fibroepithelial biphasic tumor composed of stromal and epithelial components. The patients suffering from this disease present with a large, round, mobile, fast-growing lump, and the giant PT of more than 10 cm in diameter is so uncommon. Surgery is regarded as the primary treatment, but curative efficiency of adjuvant chemotherapy and radiotherapy is so indefinite.Case presentationWe reported one case of a middle-aged woman with a huge borderline PT in the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In this study, the mean time to recurrence after VAB was 7.8 months (1–12 months). Previous studies showed the average interval to recurrence of benign PT was two years after the treatment with surgical resection [ [18] , [19] , [20] , [21] ]. The recurrence time after VAB was shorter in this study than in previous studies, which might be explained by the fact that a small amount of residual cells after VAB could not be detected on US, resulting in early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean time to recurrence after VAB was 7.8 months (1–12 months). Previous studies showed the average interval to recurrence of benign PT was two years after the treatment with surgical resection [ [18] , [19] , [20] , [21] ]. The recurrence time after VAB was shorter in this study than in previous studies, which might be explained by the fact that a small amount of residual cells after VAB could not be detected on US, resulting in early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has revealed that the survival after mastectomy and wide local excision with postoperative radiotherapy was equivalent[ 12 ]. Consequently, conservative surgery is recommended, but mastectomy should be carried out according to the following reasons: Benign or borderline tumours at least 8 cm in size, malignant PTs, or positive margins[ 13 ]. Margins of at least 1 cm with wide local excision were recommended by the National Comprehensive Cancer Network guideline for each PT grade.…”
Section: Discussionmentioning
confidence: 99%
“…Its name derives from the Greek phyllon (leaf) because of its lobed histological appearance. It is also known as cystosarcoma phyllodes, adenomatous myxoma and pseudosarcoma adenoma [[1], [2], [3]]. PTs are common in middle-aged women, with an average size of 4–7 cm and rapid growth [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as cystosarcoma phyllodes, adenomatous myxoma and pseudosarcoma adenoma [[1], [2], [3]]. PTs are common in middle-aged women, with an average size of 4–7 cm and rapid growth [1,3,4]. They are fibroepithelial tumors, composed of stromal and epithelial elements, differing from fibroadenomas (FA) by the greater abundance of the stromal component [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation